Occupational Hazards and Health Risks Among Abattoir Workers: A Narrative Review (African Journal of Biomedical Research, 2024)
The purpose of the review is to provide an informed discussion on the health and safety of workers in slaughterhouses and/or abattoirs where animals are slaughtered for human consumption and different processes and activities are performed on daily basis. Primarily, this review provides knowledge on health and safety within slaughterhouses and/or abattoirs and subsequently to identify occupational hazards and health risks associated thereon. Abattoir work can be connected to the health hazards that might result in occupational diseases and/or may exacerbate the existing ill-health of non-occupational origin. Several studies have been completed on the health and safety of workers in abattoirs and studies indicated that workers in animal-related occupations have an average knowledge to adequate knowledge of zoonotic diseases but poor knowledge of preventive measures and that employer responsibilities towards prevention and control of occupational hazards are inadequate. South Africa has enacted legislation to deal with occupational health and safety, this includes the Occupational Health and Safety Act, 85 of 1993. However, information on the development of National Guidelines on health and safety in the meat industry is still lacking. This legislation covers occupational health and safety in all workplaces and ensures that employers and workers comply with the requirements stipulated to protect the workers from hazards in the workplace. Therefore, this review recognizes that there is limited literature on the health and safety of workers and poor knowledge on identifying the types of injuries experienced and the associated risk factors, and as well as the management of these injuries in the facilities.
Keywords: Abattoirs; occupational hazards; health risks; infections; zoonosis